Functional mapping of the neuronal substrates for drug tolerance in Drosophila. - Ghezzi, A.; Al-Hasan, Y.M.; Krishnan, H.R.; Wang, Y.; Atkinson, N.S. (Behavior Genetics, 2013)
Physical dependence on alcohol and anesthetics stems from neuroadaptive changes that act to counter the effects of sedation in the brain. In Drosophila, exposure to either alcohol or solvent anesthetics have been shown to induce changes in expression of the BK-type Ca(2+)-activated K(+) channel gene slo. An increase in slo expression produces an adaptive modulation of neural activity that generates resistance to sedation and promotes drug tolerance and dependence. Increased BK channel activity counteracts the sedative effects of these drugs by reducing the neuronal refractory period and enhancing the capacity of neurons for repetitive firing. However, the brain regions or neuronal populations capable of producing inducible resistance or tolerance remain unknown. Here we map the neuronal substrates relevant for the slo-dependent modulation of drug sensitivity. Using spatially-controlled induction of slo expression we identify the mushroom bodies, the ellipsoid body and a subset of the circadian clock neurons as pivotal regions for the control of recovery from sedation.